School Motivation and Learning Strategies of Freshmen Student-Athletes of Philippine Normal University: Basis for Intervention - Vergara, Lordinio A; Aragones, Ana Katrina J (SIPATAHOENAN, 2015)
ABSTRACT: Recruited athletes are often given an admissions advantage entering college, but with less impressive academic records. The study aimed to determine the school motivation and learning strategies, the admission scores as well as the academic profile of the freshmen student-athletes. Findings reveal that most of the student-athletes have moderately developed learning skills, average intrinsic motivation, common performance anxiety associated with testing, and do have reasonable listening and attention skills in the classroom environment. The study also showed significant difference in the Writing/Research Skills and Test-Taking Strategies between the male and female student-athletes, which means that females have better study skills than the male students. On the other hand, academic difficulty is noted as an increase in their deficiency occurred during the second semester due to incomplete, dropped, and failed ratings, while significant association is found between their PNUAT (Philippine Normal University Admission Test) scores and GPA (Grade Point Average). The above mentioned findings aid the researchers in developing an intervention program, which focuses in enhancing the student-athletes academic motivation and learning strategies essential to academic success.KEY WORD: School Motivation; Learning Strategies; Academic Performance; Student-Athletes; Intervention Program.Â INTISARI: âMotivasi Sekolah dan Strategi Belajar para Mahasiswa-Atlet dari Universitas Pendidikan Filipina: Basis untuk Intervensiâ. Perekrutan atlet sering memberikan keuntungan untuk masuk diterima di perguruan tinggi, namun dengan catatan akademis yang kurang mengesankan. Penelitian ini bertujuan untuk mengetahui motivasi sekolah dan strategi belajar, skor masuk, serta profil akademik para mahasiswa-atlet. Temuan mengungkapkan bahwa sebagian besar mahasiswa-atlet telah cukup mengembangkan keterampilan belajar, motivasi intrinsik rata-rata, kecemasan kinerja umum yang terkait dengan pengujian, serta harus mendengarkan dan memperhatikan keterampilan yang wajar dalam lingkungan kelas. Penelitian ini juga menunjukan perbedaan yang signifikan dalam Keterampilan Menulis/Meneliti dan Ujian Strategi antara mahasiswa-atlet pria dan wanita, yang mana bahwa mahasiswa-atlet wanita memiliki kemampuan belajar yang lebih baik daripada mahasiswa-atlet pria. Di sisi lain, kesulitan akademik terjadi peningkatan sebagai akibat kekurangan mereka selama semester kedua, karena tidak selesai, gagal, dan turun peringkat, sementara hubungan yang signifikan ditemukan antara skor PNUAT (Tes Masuk Universitas Pendidikan Filipina) dengan IPK (Indeks Prestasi Kumulatif) mereka. Temuan tersebut di atas membantu para peneliti dalam mengembangkan program intervensi, yang difokuskan untuk meningkatkan motivasi akademik dan strategi belajar yang penting bagi para mahasiswa-atlet dalam keberhasilan akademis mereka.KATA KUNCI: Motivasi Sekolah; Strategi Belajar; Prestasi Akademik; Mahasiswa-Atlet; Program Intervensi.Â Â About the Authors: Prof. Lordinio A. Vergara is Director of the Institute of Physical Education, Health, Recreation, Dance, and Sports PNU (Philippine Normal University) in Manila, Philippines; and Ana Katrina J. Aragones is a Psychometrician at the San Beda College Alabang, Head Coach, and Volleyball Women at the PNU in Manila, Philippines. Corresponding author is: vergara.la@pnu.edu.phHow to cite this article? Vergara, Lordinio A. & Ana Katrina J. Aragones. (2015). âSchool Motivation and Learning Strategies of Freshmen Student-Athletes of Philippine Normal University: Basis for Interventionâ in SIPATAHOENAN: South-East Asian Journal for Youth, Sports & Health Education, Vol.1(2) October, pp.147-164. Bandung, Indonesia: Minda Masagi Press, APAKSI Bandung, and KEMENPORA RI Jakarta, ISSN 2407-7348.Chronicle of the article: Accepted (July 31, 2015); Revised (September 5, 2015); and Published (October 28, 2015).